Identifying and regulating emotions after acquired brain injury: the role of interoceptive sensibility - Desdentado, Lorena; Miragall, Marta; Llorens, Roberto; Navarro, María Dolores; Baños, Rosa M. (Frontiers in Psychology, 2023)
Interoceptive deficits are associated with difficulties in identifying and regulating emotions. However, research on interoception after acquired brain injury (ABI) is scarce, and its relationship with emotional difficulties in this population is unknown. This study aimed to (1) examine differences in self-reported alexithymia, performance-based emotional awareness, emotion regulation, depression, and interoceptive sensibility between ABI and control individuals; and (2) analyze the role of adaptive interoceptive dimensions in these emotional processes after ABI. Methods: Forty-three individuals with ABI and 42 matched control individuals completed the Multidimensional Assessment of Interoceptive Awareness-2, the Toronto Alexithymia Scale, the Levels of Emotional Awareness Scale, the Difficulties in Emotion Regulation Scale, and the Hospital Anxiety and Depression Scale.Results: Compared to the control group, individuals with ABI showed reduced tendency to ignore unpleasant sensations increased severity of depressive symptoms, as well as tendencies to have greater difficulties in emotion regulation and lower emotional awareness. Additionally, interoceptive dimensions such as trusting, as well as not-distracting from and not-worrying about bodily This is a provisional file, not the final typeset article sensations, played a relevant role in explaining lower alexithymia and difficulties in emotion regulation. Moreover, lower alexithymia and emotion dysregulation were related to less depressive symptoms. These relationships were invariant across ABI and control individuals.Discussion: Although individuals with ABI may have different levels of emotional abilities compared to non-ABI individuals, the relationship patterns between interoceptive and emotional processes appear to be similar between the two groups. This study suggests the potential benefit of addressing both interoceptive and emotional difficulties in treatments targeting such prevalent sequelae of ABI as depressive symptoms.